Techniques and principles of endoscopic treatment of benign gastrointestinal strictures. Issue 5 (September 2015) - Irani, Shayan; Kozarek, Richard A.
<x xml:space="preserve">Abstract</x> Purpose of review The fundamental goal of treating any stenosis is luminal enlargement to ameliorate the underlying obstructive symptoms. Symptoms depend on the etiology and the site of the stricture and may include dysphagia, nausea and vomiting, abdominal pain, obstipation, or frank bowel obstruction. This article compares the various current technologies available for the treatment of gastrointestinal stenoses with regard to ease and site of application, patient tolerance, safety and efficacy data, and cost–benefit ratio. Recent findings Recent studies indicate that gastrointestinal dilation and stenting have evolved to a point at which in many if not most situations they can be the first line therapy and potentially the final therapy needed to treat the underlying condition. Summary Following techniques and principles in the management of gastrointestinal strictures would allow for the well tolerated and effective treatment of most patients with the tools currently available today.